Adaptive-TTCM-Aided Near-Instantaneously Adaptive Dynamic Network Coding for Cooperative Cognitive Radio Networks - Wei Liang; Hung Viet Nguyen; Soon Xin Ng; Hanzo, Lajos (IEEE transactions on vehicular technology, 2016)
An adaptive dynamic network coding (ADNC) scheme conceived for cooperative cognitive radio (CCR) is proposed for devising a novel ADNC-CCR system. The system is designed for supporting communications between multiple primary users (PUs) and a common base station (BS), where the independent source information is transmitted from the PUs to the BS with the aid of multiple cognitive users (CUs) acting as relay nodes (RNs). To facilitate the recovery of the source information at the BS, the CUs invoke the ADNC technique, which is assisted by our cooperative protocol operating by exchanging the CCR-based control information between near-instantaneously adaptive turbo trellis coded modulation (ATTCM) and network coding (NC) codec, as well as between the CUs and the BS. More particularly, near-instantaneous ATTCM is employed for appropriately adjusting both the modulation mode and the code rate of the channel coding itself and of the NC, according to the near-instantaneous channel conditions. As a result, our novel ADNC-CCR system constructed on the basis of our holistic approach is capable of providing an increased throughput, despite reducing the transmission period of the PU. This reduced transmission period can also be directly translated into an increased duration for secondary communications of the CUs. In our proposed ADNC-CCR scheme, both the PUs and CUs employ our ATTCM scheme. As an additional novelty, the network encoder may also be activated in its adaptive mode for supporting the CUs, depending on the Boolean value of the feedback flags generated based on the success/failure of the ATTCM decoder and of the network decoder, which is evaluated and fed back by the BS. Quantitatively, it was found that the joint holistic design of our ATTCM-ADNC-CCR scheme is either capable of freeing up an approximately 40% of the PU's bandwidth in comparison to its noncooperative counterpart or increasing the attainable throughput by 2 bits/symbol.